Pertanggungjawaban Pidana Pelaku Kekerasan Seksual Terhadap Anak Dalam Kerangka Hukum Dan Ham Di Indonesia - Reka Saditri Acintya; Dzakyyah Ameizki Atmaja; Zaqia Salsabillah; Asep Suherman (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
Children are the nation’s next generation whose fundamental rights to live, grow, and develop safely must be guaranteed. However, along with the changing times and weak supervision, cases of sexual violence against children still frequently occur and cause serious physical and psychological impacts. Based on this, the purpose of this research is to analyze the criminal liability of perpetrators of sexual violence against children within the framework of national law and the perspective of human rights. The type of research used is normative legal research with a statutory approach, a conceptual approach, and qualitative analysis of secondary data. The results show that the criminal liability of perpetrators of sexual violence against children has been regulated in Law Number 35 of 2014 in conjunction with Law Number 17 of 2016 concerning Child Protection, as well as Law Number 12 of 2022 concerning Sexual Violence Crimes. However, in practice, there are still court decisions that are considered not to provide an optimal deterrent effect due to relatively light sanctions. Therefore, judges should place greater emphasis on child protection as victims, principles of justice, and the objectives of punishment, so that they align with human rights values and help prevent the recurrence of similar crimes. The central government’s efforts to prevent human rights violations are carried out through the establishment of regulations, stricter criminal sanctions, victim rehabilitation, and dissemination of child protection awareness.